Dielectrophoretic separation of cells using 3-D microelectrode - Zainal Abidin, Zurina; Yunus, Zalini; Markx, Gerard H. (Universiti Putra Malaysia Press, 2009)
The dielectrophoretic (DEP) separation of cell, using microelectrodes structure, has been limited to small scale due to size of the substrate. This work was carried out to extend the capability of microelectrodes system by orientating the microelectrodes in three dimensions (3-D) for larger scale dielectrophoretic separation of microorganism. The designed 3-D separation chamber consists of microelectrodes on two opposing walls. Based on the FEMLAB simulation, the electric field was seen to be generated across the chamber, rather than between adjacent electrodes in the same plane like in the small scale system. This configuration led to a stronger electric field in the bulk medium. The experimental results showed that the 3-D microelectrodes chamber behaved similar to the system with microelectrodes on one wall. The effects of the main parameters such as voltage, frequency and flow rates were similar to that of the systems with all the electrodes on one wall, but on the overall, capture more cells. A gap size between 250 â€“ 500 µm resulted in an electric field which is strong enough to hold cells while giving a reasonable cross sectional area at the same time. Although there is some improvement achieved by 3-D system, it is still not very much, as compared to the small scale system.